Impressive Response to Tandem Treatment With [90Y]DOTATOC and [177Lu]DOTATOC in Grade 3 Pancreatic Neuroendocrine Carcinoma. (July 2018) - Lorenzoni, Alice; Capozza, Antonella; Artale, Salvatore; Maccauro, Marco; Seregni, Ettore Cesare
Abstract : Abstract: Peptide receptor radionuclide therapy is an effective, well-tolerated, treatment for well-differentiated neuroendocrine tumors, resulting in a significant survival benefit and improvement of quality of life. Very few data are available on peptide receptor radionuclide therapy effectiveness in grade 3 neuroendocrine carcinomas with high somatostatin receptor expression. We report the case of a 70-year-old woman with metastatic pancreatic grade 3 neuroendocrine carcinoma who underwent 6 cycles of tandem treatment with investigational radiopharmaceuticals 90 Y-DOTATOC and 177 Lu-DOTATOC achieving an impressive response.